Struktur Cerita Rakyat Jayaprana-Layonsari dan Raden Sandubaya-Lala Seruni: Sebuah Tinjauan Stukturalisme Levi-Stauss - Ratu Agung Dharmi (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2019)
This research was conducted on two different regional folklore stories, namely Balinese folklore (Jayaprana-Layonsari) and Lombok folklore (Raden Sandubaya-Lala Seruni). This study aims to determine the comparison of the two folklore structures. The theory used is the theory of Levi-Strauss Structuralism. This research data was obtained through a library method by taking data from two folklore books entitled "Jayaprana" and "Raden Sandubaya and Lala Seruni" as well as through interview methods. The results of the study show that there are similarities and differences in the four structures of folktales that are compared. The equation is seen in geographical structure and cosmology. Geographical structure in the form of land and sea, while the cosmological structure in the form of the human world and the unseen world. Differences are seen in the techno-economic structure, Jayaprana-Layonsari folklore shows more variety in terms of people's livelihoods. In the sociology structure there are two aspects in common, one different aspect, and one aspect that has similarities as well as differences.